Factors affecting consumption patterns of neglected and underutilized species in Atacora, Northern Benin - Bankole, Bissola Malikath; Bodjrenou, Sam; Bodecker, Julia; Termote, Celine; Chadare, Flora Josiane; Hounkpatin, Waliou Amoussa (SAGE Publications, 2024)
Many recent efforts focus on promoting neglected and underutilized species (NUS) for improved nutrition, but consumption depends on various factors.With this in mind, this study aims to understand the factors associated with the consumption patterns of Adansonia digitata, Ocimum gratissimum, Vigna radiata, and Moringa oleifera by households in Atacora, northern Benin.To achieve this, a food consumption survey was carried out in 3 communes. Two villages per commune were randomly selected to carry out the food consumption frequencies of households through a 7-day recall for periods of abundance and scarcity. A multinomial regression model was used to explain the consumption frequency of species depending on socio-demographic factors and seasonality.Different parts of these different species targeted were used in various forms to prepare sauces, porridges, juices, etc. Baobab- and moringa-based foods appeared to be the most widely consumed foods, regardless of the season. Even though fresh moringa leaves sauce and baobab seeds sauce were consumed mostly in periods of scarcity. The probability of rarely consuming foods made from these species was lower for households living in Toucoutouna and Tanguiéta compared to Natitingou. Furthermore, the consumption of these foods was usually higher for mothers who were students, hairdressers or seamstresses compared to housewives ( P < 0.05).The consumption patterns then vary from species to species and are influenced by demographic factors such as household location and mother's occupation. Promoting NUS among the population is essential to increase awareness of their nutritional importance and improve their consumption.Factors Affecting Consumption of Neglected and Underutilized Species in Atacora, Northern Benin